Young Adults’ Perceptions of the Role of Self-Reliance and Trust on Help Seeking for Mental Health Problems - Abigail Meadley; Debra Rickwood; Amelia Ishikawa (Youth)
Many young people are reluctant to seek support for mental health concerns, and a preference for self-reliance has been identified as a key barrier. Yet, the conceptualisation of self-reliance and its role in help seeking is not well understood. This study examines the meaning of self-reliance for young people and how they perceive it affects help seeking, with a focus on the role of trust (both in oneself and in others). Thirty Australian young people aged 18–25 years were interviewed. A reflexive approach, incorporating both inductive and deductive coding techniques, was used to construct themes about self-reliance, trust, and help seeking for young people. Participants identified that both self-reliance and help seeking exist on a continuum from insufficient self-reliance to extreme self-reliance and excessive help seeking to unwillingness to seek help. Trust was a key component of self-reliance, and a balance between trust in oneself and trust in others was deemed necessary for self-reliance to be adaptive and for appropriate help seeking to occur. To maintain this balance, young people felt that a level of self-awareness was necessary. A high level of trust in oneself was considered to increase self-reliance, whereas a high level of trust in others increases help-seeking behaviours. Understanding the role of trust in self-reliance informs developmentally appropriate ways to address self-reliance as a barrier to mental health help seeking for young people.